From "colour and flair" to "a corporate view": evolutions in guidebook writing: an interview with Jenny Walker. Issue 2 (3rd April 2017) - Butler, Rebecca; Aatkar, Sofia
ABSTRACT: In an interview conducted by Sofia Aatkar and Rebecca Butler at Nottingham Trent University on 23 March 2017, Jenny Walker discusses her path towards professionalisation as a guidebook author. Walker contemplates the question of ethical responsibility surrounding destination development and commercial endorsement, the balance between individual and corporate identity, and the relationship between guidebook authors and their readers, before turning to consider the impact of digital technologies on her practice. Challenging the marginalisation of guidebooks within travel writing studies, Walker evidences the commercial impact of publications like Lonely Planet . However, turning to discuss her doctoral project, Walker recognises the influence of travel theories on her practice as well as how her profession as a guidebook author has, in turn, helped to shape her critical understanding of travel writing.